Simultaneous GC-FID Quantification of Main Components of Rosmarinus officinalis L. and Lavandula dentata Essential Oils in Polymeric Nanocapsules for Antioxidant Application - Perla Giovanna Silva-Flores; Luis Alejandro Pérez-López; Verónica Mayela Rivas-Galindo; David Paniagua-Vega; Sergio Arturo Galindo-Rodríguez; Rocío Álvarez-Román (Journal of Analytical Methods in Chemistry)
The essential oils (EO) of R. officinalis and L. dentata have been widely used due to their antioxidant activity. However, due to their high volatility, the loading of EO into polymeric nanocapsules (NC) represents an efficient way of retaining their effect in future topical administration. In this way, the quantitative determination of EO incorporated into NC is necessary for simultaneous monitoring of the main components of the EO during the nanoencapsulation process as well as for precise and exact dosing of the components used during the performance of in vitro and in vivo biological tests. In this study, EO were isolated by hydrodistillation in a Clevenger-type apparatus and characterized by GC-MS and GC-FID analyses. The major constituents of EO-R. officinalis were camphor (39.46%) and 1,8-cineole (14.63%), and for EO-L. dentata were 1,8-cineole (68.59%) and β-pinene (11.53%). A new analytical method based on GC-FID for quantification of free and encapsulated EO was developed and validated according to ICH. Linearity, limit of detection and quantification, and intra- and interday precision parameters were determined. The methods were linear and precise for the quantification of the main components of EO. The EO were encapsulated by nanoprecipitation and were analyzed by the GC-FID method validated for their direct quantification. The NC size was 200 nm with homogeneous size distribution. The quantification of the incorporated EO within a NC is an important step in NC characterization. In this way, an encapsulation efficiency of at least 59.03% and 41.15% of total EO-R. officinalis and EO-L. dentata, respectively, was obtained. Simple, repeatable, and reproducible methods were developed as an analytical tool for the simultaneous quantification of the main components of EO loaded in polymeric nanocapsules as well as their monitoring in biological assays.